2013
DOI: 10.4137/ijtr.s11588
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Aspect of Tryptophan Metabolism

Abstract: Mammals, including humans, can synthesize the vitamin nicotinamide from tryptophan in the liver. The resultant nicotinamide is distributed to non-hepatic tissues. We have studied the effects of changes in tryptophan–nicotinamide metabolism on niacin nutritional status. The liver plays a critical role in nicotinamide supply. Animal studies showed that the tryptophan–nicotinamide pathway is affected by physiological conditions, the presence of disease, nutrients, hormones, and chemicals. Human studies have shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 35 publications
2
73
0
2
Order By: Relevance
“…More importantly, requirements were based on studies with rats as no direct data were available for mice. Estimation of vitamin B3 requirements is not straightforward, since NAD + can also be synthesized de novo from the essential amino acid tryptophan (Trp) . Dietary Trp may thus rescue vitamin B3 deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, requirements were based on studies with rats as no direct data were available for mice. Estimation of vitamin B3 requirements is not straightforward, since NAD + can also be synthesized de novo from the essential amino acid tryptophan (Trp) . Dietary Trp may thus rescue vitamin B3 deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research from Japan reported nicotinamide synthesised from tryptophan in normal healthy Japanese to be almost equal to that from dietary intake [16]. Synthesis from tryptophan has even been suggested as the primary source of NAD in the body [14].…”
Section: Sources Of Niacin and Nadmentioning
confidence: 99%
“…In the de novo pathway, synthesis from tryptophan occurs as part of the kynurenine pathway in the so-called tryptophan-nicotinamide pathway. NAD can also be generated by recycling degraded NAD components such as nicotinamide, nicotinic acid and nicotinamide riboside in the so-called salvage pathways [6,16].…”
Section: Sources Of Niacin and Nadmentioning
confidence: 99%
“…It has been acknowledged that tryptophan is converted into numerous compounds of biological significance such as vitamins, neurotransmitters and auxins (Fukuwatari and Shibata, 2013). Among these biogenetically tryptophan-related compounds, indole-3-acetic acid (IAA) and serotonin (5-hydroxytryptamine, 5HTAM) inspired in-depth research on plant morphogenesis and growth regulators as they contribute to the possible coordinated regulation in plants (Pelagio-Flores et al, 2011;Ramakrishna et al, 2011).…”
Section: Introductionmentioning
confidence: 97%